The effect of tetrahydrocannabinol:cannabidiol oromucosal spray on cognition: a systematic review. - Motaghi, Ehsan; Ghasemi-Pirbaluti, Masoumeh; Rashidi, Mohsen; Alasvand, Masoud; Di Ciano, Patricia; Bozorgi, Hooman (European Journal of Clinical Pharmacology, 2023)
Purpose: Previous studies have shown that tetrahydrocannabinol (THC), the main psychoactive component of cannabis, can impair cognitive abilities. There is also some evidence that cannabidiol (CBD), the most abundant non-intoxicating constituent of cannabis, can attenuate these effects. The purpose of this study was to investigate the effects of THC:CBD oromucosal spray (with equal parts THC and CBD) on cognition compared with control conditions in human studies. Methods: A systematic literature search was performed on four major bibliographic databases. Studies were included in the present review if they evaluated the cognitive effects of THC:CBD oromucosal spray compared with a control condition. Results: Ten studies were identified (7 on patients with multiple sclerosis, 1 on those with Huntington, and 2 on healthy volunteers) with 510 participants in total. There was considerable heterogeneity among the studies in terms of dose and duration of administration. All studies have used an equal or nearly equal dose of THC and CBD. Conclusions: Although the results across studies were somewhat inconsistent, most evidence revealed that there is no significant difference between THC:CBD oromucosal spray and control treatments in terms of cognitive outcomes. However, more trials are needed with longer follow-up periods, and dose considerations, particularly comparing lower and higher doses of the spray.